Pengaruh People, Process, dan Physical Evidence terhadap Kepuasan Konsumen pada Hydealson Barbershop di Kota Denpasar - Lim, Hellen; Astawa, I Putu Putra; Agustina, Made Dian Putri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was conducted to determine the influence of people, process, and physical evidence on consumer satisfaction at Hydealson Barbershop. The number of samples used in this study was 90 respondents using the sample determination method, namely purposive sampling. The data collection methods are observation, interviews, literature studies, documentation, and questionnaires. While the data analysis techniques in this study are validity test, reliability test, classical assumption test, multiple liner regression analysis, determination coefficient test, t test, and f test. Based on the results of the study, it can be seen that people, process, and physical evidence have a positive and significant effect on consumer satisfaction. The magnitude of the influence of people, process, and physical evidence on consumer satisfaction is 77.2%. Based on the results of the study, Hydealson Barbershop should pay more attention to customer satisfaction by providing good service, carrying out the hair cutting process according to consumer wishes, and providing a comfortable service environment for consumers, so as to increase consumer satisfaction and be able to increase consumer visits at Hydealson Barbershop.